The Maastrichtian sea level rise - GULLENTOPS, F (Annales de la Société géologique de Belgique, 1986)
L'hypothèse d'un maximum eustatique Maastrichtien de plus de 500 m n'est pas supportée par les faits géomorphologiques et sédimentologiques en Ardenne. The maximum sea level rise during the Maastrichtian has been much less than the 500 m claimed by some recent authors on this subject. Sedimentological and geomorphological arguments against such an hypothesis are forwarded.